Employer branding: strategier för att betraktas som en attraktiv arbetsgivare : En fallstudie av banksektorn i Piteå - Lindfors, Lisa; von Ahn, Annica (2013)
Societys constant evolution and the constant changes on the market forces organizations to adapt themselves and the products they offer to stay competitive. The framework of marketing has shifted, to some degree, from the centralized view on products to more of a focus on a organization´s employees. Service companies have the most to gain by having the right employees, because they are the person in the organization who does the service the company sells.The new marketing focus on employees shows the importance of internal marketing, companies marketing their own brand to their employees. With this comes the complexity that all employees bring in all their humanity. Needs and expectations, motivation and attitudes are some components, which influences how employees functions and the level of involvement they have in their workplace.Our purpose with this study has been to investigate how companies handle this complexity through the subject employer branding. To be able to get some depth to our study we had to narrow our scope and have chosen to investigate the banking sector. The banking sector was chosen because of their need for competent and knowledgeable personnel. Another reason are that the products the bank offers the consumer is hard to differentiate from the products from other banks, therefore the personnel and how they handle companies are even more important.The questions the study are trying to answer are:How do banks utilize employer branding?Why does banks utilize employer branding?The theoretical basis of our study is based on relevant literature and scientific articles. The search words we used are: “employer brand”, “organisationskultur”, “personalidé”, “motivation”, “intern marknadsföring”, “corporate branding”, “behov” and “attityder”. The gathered data is based on a qualitativestudy with semistructured interview with, by the banks, chosen personnel who work with the subject.Our analysis and conclusion shows that companies actively work with employer branding through communication, the ...